"Urchin pinning": Behavioural observations reveal how hungry urchins actively prey upon their sea star predators. (23rd March 2021) - Clements, Jeff C.; Dupont, Sam; Jutfelt, Fredrik
Abstract: Green sea urchins ( Strongylocentrotus droebachiensis ) are dominant components of benthic ecosystems that form aggregations and can transform entire kelp forests into barren systems. While these urchins are known to unwittingly consume practically anything in their path while grazing, detailed descriptions of active predatory behaviour on known predators (i.e., predator–prey reversal) are undocumented. Here, we use laboratory observations to describe the behavioural tactics used by starved S. droebachiesis to actively attack and consume sea stars, Crossaster papposus —a known predator of S. droebachiensis . We observed urchins preying on three separate sea stars, with one being substantially consumed by urchins within 24 hr. Urchins exhibited a direct mode of attack on sea stars by individually mounting and consuming the tips of the arms. Interestingly, we did not observe any conflict between individual urchins for attacking the sea star despite there being ≈80 starving urchins in the tank (and only 10–12 arms on the sea stars). Some sea stars did not attempt to escape urchin predation at all, while others attempted to escape by fleeing and lifting arms on top of the urchins. Given that sensory perception in sea stars is largely derived from the arm tips, we suggest that urchins directly attack and consume many sea star arm tips in an attempt to "pin" sea stars before consuming them. As such, we term this predatory behaviour "urchin pinning." These observations ultimately provide the first detailed behavioural documentation of how urchins actively prey on a known predator and provide a basis for a wealth of future research. Abstract : Damage inflicted on sea star ( C. papposus ) by green sea urchins ( S. droebachiensis ) within 24 hr of the sea star being placed in a tank with ≈80 starving urchins.